Prevention Strategy of Chemotherapy-Induced Nausea and Vomiting (CINV) with Olanzapine: Alternative Option - Pondawinata, Marizki (International Journal of Advanced Multidisciplinary, 2022)
Chemotherapy-induced nausea and vomiting (CINV) is a major problem for patients who use chemotherapy and can lower the quality of life for many cancer patients. If the patient is continuing chemotherapy treatment, then the patient can be certain to experience CINV. Current CINV prevention strategies primarily use 5-hydroxytryptamine-3 receptor antagonists (5HT3-RAs), dexamethasone, and/or neurokinin-1 receptor antagonists (NK-1 RAs). However, these preventive therapies have not been fully implemented, especially the use of NK-1 RAs because of the high cost. In addition, a standard therapy for CINV prevention is still not effective in controlling CINV symptoms. One alternative CINV preventive therapy option is to use olanzapine. It is an antipsychotic drug that can be used as a preventive therapy for CINV off-label. The purpose of this study is to explain the utilization of olanzapine as alternative choice of antiemetic therapy in preventing CINV.